2018
DOI: 10.1093/infdis/jiy478
|View full text |Cite|
|
Sign up to set email alerts
|

Therapeutic Implications of Human Umbilical Cord Mesenchymal Stromal Cells in Attenuating Influenza A(H5N1) Virus–Associated Acute Lung Injury

Abstract: Our results suggest that UC-MSCs are effective in restoring AFC and APP in H5N1-associated ALI and confer functional in addition to practical advantages over conventional BM-MSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
105
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(107 citation statements)
references
References 38 publications
1
105
0
1
Order By: Relevance
“…Those mice in receipt of MSCs following infection showed improved survival rates, lung histopathology and reduced serum and BALF inflammatory cytokine and chemokine concentrations compared to the control group [99]. While most studies explore the potential of BM-derived MSCs, a report comparing their performance versus umbilical cord (UC) derived MSCs in a human alveolar epithelial cell and mouse models of H5N1 infection demonstrated better restoration of alveolar fluid clearance and protein permeability with UC-MSCs [100].…”
Section: Mscs In Pre-clinical Models and Clinical Investigations Of Amentioning
confidence: 99%
“…Those mice in receipt of MSCs following infection showed improved survival rates, lung histopathology and reduced serum and BALF inflammatory cytokine and chemokine concentrations compared to the control group [99]. While most studies explore the potential of BM-derived MSCs, a report comparing their performance versus umbilical cord (UC) derived MSCs in a human alveolar epithelial cell and mouse models of H5N1 infection demonstrated better restoration of alveolar fluid clearance and protein permeability with UC-MSCs [100].…”
Section: Mscs In Pre-clinical Models and Clinical Investigations Of Amentioning
confidence: 99%
“…Umbilical cord derived MSC were able to restore the alveolar epithelial cell functions as seen by increased alveolar fluid clearance and decreased protein permeability in avian influenza (H5N1) virus lung injuries in mice models. [112] MSCs are resistant to viral infections, and recently it has been established that intrinsically expressed interferon stimulated genes (ISG) protect stem cells against viral infection. The study demonstrated that induction of intrinsic ISG in human MSCs constitutively increased the expression of antivirals (IFI6, ISG15, CCL2, SAT1, PMAIP1 and IFITM1).…”
Section: Introductionmentioning
confidence: 99%
“…These effects have also been observed using conditioned medium and exosomes of UC-MSCs. Notably, UC-MSCs treatment slightly improved survival of A/H5N1-infected mice and significantly improved fluid clearance in the alveolar airspace, compared to BM-MSCs and controls [85].…”
Section: Msc Therapy In Viral Infections: Preclinical and Clinical Apmentioning
confidence: 92%